PENGEMBANGAN BUKU CERITA KARICA SEBAGAI PELESTARIAN BAHASA KRAMA ALUS ANAK USIA 5-6 TAHUN DI TK PUTRA PERTIWI XVIII PAYAMAN - Khoirotun Nissa; Akhmadi Putro Aji pangestu; Narendradewi Kusumastuti (LPPM STAI La Tansa Mashiro, 2026)
This study aims to develop a learning medium, the Karica Storybook, as an effort to preserve the Javanese krama alus language for children aged 5–6 years at Putra Pertiwi Kindergarten XVIII Payaman. This study used a Research and Development (R&D) method with the ADDIE development model, which includes five stages: analysis, design, development, implementation, and evaluation. The results indicate that the Karica Storybook has a very high level of feasibility. This is demonstrated by the validation results from material experts (95%), validation from media experts (95.83%), and group trials by users (teachers) (97.77%). Overall, the media's feasibility level reached 94.81%, which falls into the categories of very feasible, very effective, and very efficient. The Karica Storybook has been proven to increase children's interest in learning, help them understand new vocabulary, and support their ability to use Javanese krama alus in simple contexts. Therefore, this medium can be used as an innovative learning alternative to support the preservation of regional languages in early childhood.